A SEMANTIC ANALYSIS OF DIFFERENCE LEXICAL CHOICES IN QURAN TRANSLATION OF INDONESIAN AND DUTCH VERSIONS - Rika Astari; Betty Mauli Rosa Bustam (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
This study aims to compare two translations of the Quran, which were known for the first time among Indonesian Muslims around 1930-1950. De Heilig Qoeran, translated into the Dutch language written by Soedewo and Terjemah Quran Karim was translated into the Indonesian language written by Mahmud Yunus. The material object of this study was: De Heilig Qoeran, which was translated Quran into Dutch language, written by Soedewo and Terjemah Quran Karim was translated Quran into Indonesian language written by Mahmud Yunus. The formal object was the difference between these two translations lies not only in the differentiation of language but also the differences in lexical choices given by the two translators in certain verses in their book of translation. This research belongs to a descriptive qualitative. Data were analyzed using the matching method (metode padan). The difference in its meaning was analyzed by lexical decomposition. The results of this study indicate that the lexical choice differences in the two translated books produce significant differences in meaning over the entire verse. De Heilig Qoeran tends to choose lexicon, which has logical meanings while the Tafsir Quran Karim emphasizes supernatural things, especially related to the miracles of the prophets.